2010
DOI: 10.1038/mp.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

TMEM132D, a new candidate for anxiety phenotypes: evidence from human and mouse studies

Abstract: The lifetime prevalence of panic disorder (PD) is up to 4% worldwide and there is substantial evidence that genetic factors contribute to the development of PD. Single-nucleotide polymorphisms (SNPs) in TMEM132D, identified in a whole-genome association study (GWAS), were found to be associated with PD in three independent samples, with a two-SNP haplotype associated in each of three samples in the same direction, and with a P-value of 1.2eÀ7 in the combined sample (909 cases and 915 controls). Independent SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(151 citation statements)
references
References 55 publications
(75 reference statements)
7
140
1
2
Order By: Relevance
“…An initial GWAS found association of a TMEM132D SNP (rs7309727) as well as a haplotype combining this and another SNP (rs11060369). Risk genotypes were associated with higher TMEM132D mRNA expression in human postmortem frontal cortex, results further supported by a mouse model in which high anxiety-related behavior was associated with a Tmem132d SNP and correlated with expression of Tmem132d mRNA in the anterior cingulate cortex (Erhardt et al, 2011). In a subsequent meta-analysis of eight independent case-control samples, genome-wide significant associations of rs7309727 and the haplotype of rs7309727-rs11060369 were reported when the analysis was restricted to European ancestry cases with primary PD (Erhardt et al, 2012).…”
Section: Common Genetic Variationsupporting
confidence: 50%
“…An initial GWAS found association of a TMEM132D SNP (rs7309727) as well as a haplotype combining this and another SNP (rs11060369). Risk genotypes were associated with higher TMEM132D mRNA expression in human postmortem frontal cortex, results further supported by a mouse model in which high anxiety-related behavior was associated with a Tmem132d SNP and correlated with expression of Tmem132d mRNA in the anterior cingulate cortex (Erhardt et al, 2011). In a subsequent meta-analysis of eight independent case-control samples, genome-wide significant associations of rs7309727 and the haplotype of rs7309727-rs11060369 were reported when the analysis was restricted to European ancestry cases with primary PD (Erhardt et al, 2012).…”
Section: Common Genetic Variationsupporting
confidence: 50%
“…Recent studies have shown a possible role of transmembrane gene 132D (TMEM132D) in the etiology of PD. 45,46 It might, therefore, be relevant to analyse these genes in future studies of PD.…”
Section: Discussionmentioning
confidence: 99%
“…The first data set originated from a panic disorder study 6 with a total of 299 468 SNPs, where 211 cases and 222 controls have been retained after standard quality control measures. Computing the difference of correlation coefficients across all pairs and choosing a P-value threshold of 1.0Â10 À5 resulted in a retention of 373 153 SNP pairs.…”
Section: Real Datamentioning
confidence: 99%